2022
DOI: 10.3389/fgene.2022.976850
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a novel cuproptosis-related long noncoding RNA signature for predicting the outcome of prostate cancer

Abstract: Background: Prostate cancer (PCa) is one of the most common tumors of the urinary system. Cuproptosis is a novel mode of controlled cell death that is related to the development of various tumor types. However, the functions of cuproptosis-related long noncoding RNAs (CRLs) in PCa have not yet been well studied.Methods: In this study, data of PCa patients were obtained from The Cancer Genome Atlas (TCGA) and from the Changhai Hospital. Univariate and multivariate Cox regression analyses and LASSO regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, in PCa, studies related to cuproptosis are still in the preliminary stage and most of them have focused on cuproptosis-related long non-coding RNA (lncRNA). Several studies have now reported that cuproptosis-related lncRNA have a better prognostic role in predicting PCa ( 43 , 44 ). However, studies on cuproptosis-related coding genes in PCa are rarely reported, and the role of cuproptosis in PCa remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, in PCa, studies related to cuproptosis are still in the preliminary stage and most of them have focused on cuproptosis-related long non-coding RNA (lncRNA). Several studies have now reported that cuproptosis-related lncRNA have a better prognostic role in predicting PCa ( 43 , 44 ). However, studies on cuproptosis-related coding genes in PCa are rarely reported, and the role of cuproptosis in PCa remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Many tumor tissues tend to accumulate high concentrations of copper due to its role in cancer, and copper chelators, including trinitrate and tetrathiomolybdate, have been used in cancer treatment [16]. Cuproptosis, a novel cell death pathway that is different from apoptosis, programmed necrosis, autophagy, and ferroptosis, has recently been identi ed [17] and was reported to participate in the development and progression of multiple cancers [18]. However, the role of cuproptosis in CRC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cuproptosis, a novel cell death pathway, has been identi ed, which is different from apoptosis, programmed necrosis, autophagy, and ferroptosis [17] . It has been reported that cuproptosis participates in the development and progression of multiple cancers [18] .…”
Section: Introductionmentioning
confidence: 99%